1993
DOI: 10.1063/1.354032
|View full text |Cite
|
Sign up to set email alerts
|

Fractal formation in a-Si:H/Ag/a-Si:H films after annealing

Abstract: The crystallization behavior of a-Si:H/Ag/a-Si:H sandwich films has been studied in detail. Fractals of Si caused by metal enhanced crystallization appear after annealing at 350–600 °C. The fractal dimension decreases (the Si fractals become more open) with the increasing annealing temperature. The number density of fractals increases at 350–450 °C and turns to decrease at 500–600 °C. The average fractal size increases from 350 to 550 °C and shows a decreasing tendency at 600 °C. The formation of fractals can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 13 publications
0
39
2
Order By: Relevance
“…Ag-induced crystallization of a-Si is also reported by some researchers. Bian et al [18] reported recrystallization of a-Si with 3:1 Ag to Si ratio. Scholz et al [19] reported the recrystallization of a-Si with 3:4 Ag to Si ratio and tens of hours of annealing at 530 1C.…”
Section: Resultsmentioning
confidence: 98%
“…Ag-induced crystallization of a-Si is also reported by some researchers. Bian et al [18] reported recrystallization of a-Si with 3:1 Ag to Si ratio. Scholz et al [19] reported the recrystallization of a-Si with 3:4 Ag to Si ratio and tens of hours of annealing at 530 1C.…”
Section: Resultsmentioning
confidence: 98%
“…Presence of certain metal layers e.g., Al, Ag, Ni, and Au on amorphous Si (a-Si) films helps to crystallize a-Si [1][2][3][4]. The process is known as metal induced crystallization (MIC) which lowers the crystallization temperature of amorphous semiconductors [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Russell et al 3 reported the crystallization of a-Si at about 485°C using an a-Si/Cu layer. Bian et al 4 reported the crystallization of hydrogenated a-Si (a-Si:H) in an a-Si:H/Ag/a-Si:H structure above 350°C. In these studies, the metal-silicide phase, which acts as a source to degrade the electrical characteristics, could remain at the center region of the transistor channel after the completion of the crystallization, and the crystallization velocity is completely dependent on the thermal diffusivity of the metal-silicide crystallization mediator.…”
Section: Introductionmentioning
confidence: 99%